Layanan Konseling Keterampilan Hidup dalam Program Pendidikan Lifeskills di Panti Sosial Bina Remaja dan Karya Wanita ”Majar Tabela” Palangka Raya - Asep Solikin; Endang Sri Suyati; Fahruddin Arfianto (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2017)
Lifeskills counseling attempts to help clients gain strength and eliminate the weakness of their thinking and acting skills; and gain an understanding of the language of skills, namely the ability to think and analyze their behavior in the form of skills. The purpose of this community service is to give lifeskill counseling services intensively to the participants in the program through the implementation of lifeskill counseling activities in the lifeskills program at the Social House of Bina Remaja dan Karya Wanita (PSBRKW) “Majar Tabela” Palangka Raya of Central Kalimantan Province. Implementation of lifeskill counseling services truely has a strong impact on the anchoring process for participants who are participating in the program so that the participants have the ability to understand the most useful affective values of their lives after leaving the program: first, they understandthe others; Second, they are be able to anticipate, recognize, and strive to meet the needs of friends around them; Third, they are be able to feel the needs of others' development and try to increase their abilities; Fourth, they are be able to open opportunities through association with various people and able to overcome the problem of difference.